ISens: A Fiber‐Based, Highly Permeable and Imperceptible Sensor Design (Adv. Mater. 37/2021). Issue 37 (14th September 2021) - Stockinger, Thomas; Wirthl, Daniela; Mao, Guoyong; Drack, Michael; Pruckner, Roland; Demchyshyn, Stepan; Steiner, Melanie; Egger, Florian; Müller, Uwe; Schwödiauer, Reinhard; Bauer, Siegfried; Arnold, Nikita; et al.
Abstract : Paper‐Based Sensors iSens are flexible, foldable, and translucent paper‐based sensors. The porous substrates consist of a fiber structure that is highly permeable to liquids. Interdigital electrodes made of ultrathin copper are individually designed by one step laser ablation. This iSens platform, presented by Martin Kaltenbrunner and co‐workers in article number 2102736, will contribute to a new generation of imperceptible sensors seamlessly integrated into smart composite materials.